Teaching Reading Narrative Text Using Story Face in Vocational High School - Zumaroh Intan Syafitri; Ismawati Ike Nugraeni; Abdul Ngafif (Scripta : English Department Journal, 2021)
The aims of this research are to describe the students‘ reading achievement and to find out the effectiveness of using story face in teaching reading narrative text. This research is quantitative using quasi-experimental design with purposive sampling technique. The population was tenth grade students and the sample was the students of X TKR 2 consist of 37 students as experimental group and X TKR 13 consist of 33 students as control group. The technique of collecting data are making instrument, expert judgment and conducting pre-test, treatment and post-test. The pre-test mean score in experimental class was 70.92 and control class was 70.55. Meanwhile, the post-test mean score in experimental class was 68.54 and control class was 67.76. It was obtained that z-value was 0.133 and the z-table was 1.96 for alpha (α) 5%. The z-value was lower than z-table (0.133<1.96) It means that Ha was rejected and Ho was accepted. Therefore, the researcher concludes that story face was ineffective in teaching reading narrative text at the tenth grade students of SMK TKMT Kebume in the academic year of 2019/2020.